Educational Media Optimization for Museum Keris Nusantara’s Masterpiece Collections Using 3D Interactive Technology - Albertus Agung Yuwono; Ardianna Nuraeni; Nur Saptaningsih; Bayu Dewa Murti; Dyah Ayu Nila Khrisna (Universitas Pendidikan Ganesha, 2025)
People's perception of museums as old-fashioned and static places is one of the causes of low public interest in visiting museums. This problem is also experienced by Museum Keris Nusantara (MKN) Surakarta, Indonesia. This research aims to optimize the educational media of the Masterpiece collection of Museum Keris Nusantara through the use of interactive 3D technology. This type of research is qualitative research. The subjects of this research consisted of the Head of UPTD Museum of Surakarta City, Staff of Museum Keris Nusantara (MKN), and 50 respondents of visitors or users of the KRIS application (for application quality testing). This research uses several data collection techniques, namely Interviews, Observations, KRIS application trials, and Questionnaires. The collected data were analyzed descriptively, qualitatively, and quantitatively. Research findings in the form of questionnaires showed 92% of respondents stated that the quality of KRIS was very good, 96% thought the quality of KRIS information was very comprehensive, 94% stated that they were very satisfied using KRIS, and 98% thought KRIS was very useful for understanding MKN's masterpiece collection. This program is effective in increasing the capacity of human resources at MKN and enriching the visitor experience through interactive and interesting digital educational media.